Outbreak Of Klebsiella pneumoniae Carbapenemase-Producing Klebsiella aerogenes Strains In A Tertiary Hospital In China - Hao M (Infection and Drug Resistance, 2019)
Min Hao,1,2 Zhen Shen,1,2 Meiping Ye,1,2 Fupin Hu,1,2 Xiaogang Xu,1,2 Yang Yang,1,2 Shi Wu,1,2 Dongfang Lin,1,2 Xiaohua Qin,1,2 Minggui Wang1,2 1Institute of Antibiotics, Huashan Hospital, Fudan University, Shanghai, People’s Republic of China; 2Key Laboratory of Clinical Pharmacology of Antibiotics, Ministry of Health, Shanghai, People’s Republic of ChinaCorrespondence: Xiaohua QinInstitute of Antibiotics, Huashan Hospital, Fudan University, No. 12 Middle Urumuqi Road, Huashan Hospital, Shanghai, People’s Republic of ChinaTel +862152888195Email 0456240@fudan.edu.cnPurpose: This study aimed to evaluate the molecular characteristics and prevalence of clinical carbapenem-resistant Klebsiella aerogenes (CRKA), collected during an outbreak in a Chinese tertiary hospital.Methods: Antimicrobial susceptibility test, using 17 antibiotics, was performed on 14 CRKA isolates. The strains were examined for the presence of β-lactamase genes by PCR, and efflux pump phenotype was determined by efflux pump inhibition test. Presence of outer-membrane porins was examined. Clonal relatedness among the isolates was investigated by pulsed-field gel electrophoresis (PFGE). S1 nuclease-PFGE and plasmid incompatibility group analysis were performed to determine plasmids, and the genetic environment of blaKPC-2 was analyzed. Epidemiological data were collected via chart review.Results: The 14 CRKA isolates were all resistant to carbapenems; five distinct groups (PFGE types A–E) were observed. All 14 isolates carried the blaKPC-2 gene. S1 nuclease-PFGE indicated the size of blaKPC-2-carrying plasmids to range from 20 kb to 200 kb, and the 14 plasmids belonged to various incompatibility groups. The most frequent genetic environment of blaKPC-2 was Tn1721- blaKPC-2-ΔTn3-IS26. PFGE type A group, including 11 KPC-2-producing clinical isolates, was primarily responsible for dissemination.Conclusion: Our findings suggest both transposons and vertical transmission to contribute to the transformation of blaKPC-2. The results strongly suggest strict implementation of infection control of CRKA, in healthcare facilities.Keywords: carbapenem resistance, Klebsiella aerogenes, Klebsiella pneumoniae carbapenemase, plasmid, genetic environment, outbreak